A method for restoring sedimentary sequence original structural profiles: A case study of Miocene strata from the northern continental slope of the South China Sea. (May 2019) - Wang, Yeyong; Guoqiang, Xu; Pang, Xiong; Zuo, Yinhui; Liu, Baojun; Han, Jianhui; Chen, Mei; Guo, Wei
Abstract: Most sequence stratigraphy models have been derived from the observation of seismic profiles, which still retain the original form of the sedimentary stage. For folded and fractured formations, there is no way to establish a full view of the basin-wide continuous stratal configuration. This paper presents an approach to restore the sedimentary sequence original structural profile through a process of segmented line-drawing of seismic events, reassembly and modification. We use a case study from the Pearl River Mouth Basin, in the South China Sea, to demonstrate the principle and method of this technology. After restoration, we obtained a basin-wide, sedimentary stage form and continuous sequence stratigraphic structure profiles, and thus further investigated the sedimentary landforms, palaeo-water depth, sedimentary systems, stacking pattern, stratal configuration, parasequence sets and systems tract, which may be ambiguous in conventional seismic profiles. This approach may be applied to the study of basin and sequence stratigraphy and basin sedimentary process. Highlights: A new technique for restoring the sedimentary sequence original form seismic profile by the method of line-drawing. Remove faults and folds, a complete sequence stratigraphic profile of the entire basin can be displayed on A4 paper. The original form profile can be used to determine the genetic unit (systems tract) and sedimentary environment. To estimate the water depth and determine the source rock (condensed section) buried in deep depth.